Sensitivity Treatments for Teeth with Molar Incisor Hypomineralization: Protocol for a Randomized Controlled Trial - Mendonça, Fernanda L; Di Campli Regnault, Fabiana Giuseppina; Di Leone, Camilla C L; Grizzo, Isabella C; Bisaia, Aliny; Fragelli, Camila [UNESP]; Oliveira, Thais M; Magalhães, Ana C; Rios, Daniela (JMIR Publications, 2022)
Background: The sensitivity of teeth with molar incisor hypomineralization (MIH) can affect children s quality of life and is a challenging problem for dentists. Remineralizing agents such as sodium fluoride varnish seem to reduce the sensitivity of teeth with MIH, but long-Term clinical trials with large samples are still needed for more evidence about its effectiveness as a desensitizing agent before its clinical recommendation. Objective: This randomized clinical trial aims to compare three treatment interventions for teeth with MIH and hypersensitivity. Methods: A total of 60 children aged 6-10 years presenting with at least one first permanent molar with sensitivity and no loss of enamel will be randomly assigned to three groups: The control group (sodium fluoride varnish; Duraphat, Colgate); experimental group I (4% titanium tetrafluoride varnish); and experimental group II (a coating resin containing surface prereacted glass-ionomer filler; PRG Barrier Coat, Shofu). The sodium fluoride varnish and 4% titanium tetrafluoride varnish will be applied once per week for 4 consecutive weeks and the PRG Barrier Coat resin will be applied in the first session and the application will be simulated the following 3 weeks to guarantee the blinding of the study. The primary outcome will be sensitivity level measured at different moments (before each material application, immediately after application or simulation, and 1, 2, 4, and 6 months after the last application/simulation) by one examiner using the Wong-Baker FACES Pain Rating Scale, the Schiff Cold Air Sensitivity Scale, and the FLACC (Face, Legs, Activity, Cry, Consolability) scale. As secondary outcomes, parental satisfaction and child self-reported discomfort after the treatment will be measured with a questionnaire prepared by the researcher. The data will undergo statistical analysis and the significance level will be set at 5%. Results: The project was funded in 2018, and enrollment was completed in November 2019. The recruitment of participants is currently underway and the first results are expected to be submitted for publication in 2022. Conclusions: If found effective in reducing the patient s sensitivity long term, these agents can be considered as a treatment choice, and the findings will contribute to the development of a treatment protocol for teeth with sensitivity due to MIH.
Keywords: dental care; dentistry; fluoride; molar incisor hypomineralization; pediatric dentistry; sensitivity